History of the Pauline Corpus in Texts, Transmissions and Trajectories : A Textual Analysis of Manuscripts from the Second to the Fifth Century - Stevens, Chris S., (Texts and Editions for New Testament Study ;, 2020)
In History of the Pauline Corpus in Texts, Transmissions, and Trajectories , Chris S. Stevens examines the Greek manuscripts of the Pauline texts from P46 to Claromontanus. Previous research is often hindered by the lack of a systematic analysis and an indelicate linguistic methodology. This book offers an entirely new analysis of the early life of the Pauline corpus. Departing from traditional approaches, this text-critical work is the first to use Systemic Functional Linguistics, which enables both the comparison and ranking of textual differences across multiple manuscripts. Furthermore, the analysis is synchronically oriented, so it is non-evaluative. The results indicate a highly uniform textual transmission during the early centuries. The systematic analysis challenges previous research regarding text types, Christological scribal alterations, and textual trajectories.